2015
DOI: 10.1136/bmjopen-2014-006719
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against nurses in Chinese hospitals: a cross-sectional survey

Abstract: ObjectivesTo determine the prevalence of workplace violence that Chinese nurses have encountered, identify risk factors and provide a basis for future targeted interventions.SettingHeilongjiang, a province in northeast China.MethodsA cross-sectional survey.ParticipantsA total of 588 nurses provided data. There were also in-depth interviews with 12 nurses, 7 hospital administrators and 6 health officials.ResultsA total of 7.8% of the nurses reported physically violent experiences and 71.9% reported non-physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
175
5
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 38 publications
20
175
5
9
Order By: Relevance
“…In this study, 15.5% respondents were found to be exposed to physical violence which was higher than the results of the study conducted in China (5.8%) 24 , Southern Thailand (3.1%), 19 Egypt(9.3%) 6 and lower than the study conducted in Iran (49.9%), 7 North of Iran (29.1%), 25 Palestine (20.8%). 15 Studies conducted in China 22 and Iran 7 showed that the perpetrators of the physical violence were mostly the relatives of patients.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…In this study, 15.5% respondents were found to be exposed to physical violence which was higher than the results of the study conducted in China (5.8%) 24 , Southern Thailand (3.1%), 19 Egypt(9.3%) 6 and lower than the study conducted in Iran (49.9%), 7 North of Iran (29.1%), 25 Palestine (20.8%). 15 Studies conducted in China 22 and Iran 7 showed that the perpetrators of the physical violence were mostly the relatives of patients.…”
Section: Resultscontrasting
confidence: 54%
“…16,18,19,[24][25][26] This difference may be due to cultural differences and the way in which violence is described. Similar findings were showed in Ghana.…”
Section: Resultsmentioning
confidence: 99%
“…As formas de violência física relatadas foram: arranhar, beliscar, chutar, esmurrar, dar tapas, apertar contra a parede, morder, agredir com objetos, entre outras (SANTOS ET AL., 2011). Em contraponto, estudo realizado na China aponta que a violência não física é expressivamente superior (71%) no relato de profissionais de enfermagem em comparação à violência física (7,8%), destacando-se a agressão verbal e o assédio sexual (JIAO ET AL., 2015).…”
Section: Resultsunclassified
“…As formas de violência física relatadas foram: arranhar, beliscar, chutar, esmurrar, dar tapas, apertar contra a parede, morder, agredir com objetos, entre outras (SANTOS ET AL., 2011). Em contraponto, estudo realizado na China aponta que a violência não física é expressivamente superior (71%) no relato de profissionais de enfermagem em comparação à violência física (7,8%), destacando-se a agressão verbal e o assédio sexual (JIAO ET AL., 2015).Em relação à violência ocupacional presente em unidade de pronto atendimento hospitalar, identificou-se que 76,7% dos trabalhadores de enfermagem referiram ser vítima de algum tipo de violência (VASCONCELLOS; ABREU; MAIA, 2012). Os acompanhantes de pacientes assistidos foram apontados como principais responsáveis, e que a totalidade das ações violentas se deu na forma de agressão verbal.…”
unclassified
“…Although CHCs converted from private hospitals saw more patients, their overall clinical expertise was poor compared with that of government-run or hospital-managed CHCs. 21 Arguably, setting up primary care services in big hospitals with the support of tests and procedures, and specialists could be an additional transition measure to introduce general practice and help patients gain trust in this "new" discipline. 22 As primary care is a relatively new discipline to medical schools in China, very few of them have general practice departments; additionally, exposure to primary care at the undergraduate level is minimal, a situation further compounded by the low status of the discipline.…”
Section: Discussionmentioning
confidence: 99%